REMEDIASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA DENGAN MENGGUNAKAN WAWANCARA KLINIS PADA MATERI PERBANDINGAN - Manurung, Cilacili (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aimed to fix student?s error in narrative problem by using clinical interviews in comparison material. This research uses pra experiment method with qualitative form. The subjects in this research are 5 of 36 students in VIII G that did error in pre test. Based on the research result from 5 student of VIII class, is known that they did errors in solvingnarrative problemin comparison material. Kind of errors are: reading error, understanding, transformation, ability process, final result error. Analyses data result shows that remediation by using clinical interviews can help fixing student?s error in comparison material.In pre test, subjects errors are five, while in post test, subjects errors after given remediation are two. From pre test and post test result, we can see that student?s errors decrease after given remediation by using clinical interviews. So, we can conclude that clinical interviews is one of methods that can use to fix student?s error in narrative problem in comparison material.Keywords: Remediation, Student?s error, Clinical Interviews